Activity Book Pengenalan Hewan Harimau Sumatera - Dhidit Prayoga; Eliya Febriyeni (Jurnal Mahasiswa Kreatif, 2023)
The Sumatran tiger is the only type of tiger remaining in Indonesia, other types such as the Balinese tiger and Javanese tiger have become extinct. The lack of introduction to the Sumatran Tiger animal, and the lack of interest in existing books about the Sumatran Tiger, means that children aged 6-8 years do not fully know the Sumatran Tiger animal. Therefore, this design was created to create a new educational media that is appropriate and fun for children aged 6-8 years to learn about the Sumatran tiger. This activity book contains narratives and information about the characteristics of the Sumatran Tiger, how to breed, how to survive, the decline in the Sumatran Tiger population, and contains illustrations and activity content in the form of mazes, counting, find the different, coloring and flashlight pages. Using the glass box method, the design systematically applies the stages of preparation, incubation, illumination and verification. Through these stages, the main media is produced in the form of activity books and supporting media, namely t-shirts, x-banners, string bags, posters, stickers and keychains.